Injuries and Illness Prevalence Prior to Competition in Goalball Players. (September 2019) - Gajardo, Rubén; Aravena, Carmen; Fontanilla, Macarena; Barría, Mauricio; Saavedra, Cristhian
Introduction: Goalball is a sport specifically created for persons with visual impairments. In spite of all benefits that participating in sport-related activities brings to athletes with visual impairments, there is also the inherent, associated risk of being injured. Competing presenting injuries or illnesses or both not only decrease performance in contests but also increase the risk of acquiring new injuries. There is no information available regarding prior-to-competition injuries or illnesses in athletes with visual impairments. The objective of this research is to determine prevalence of injuries and diseases in athletes prior to a sport-competitive event. Method: A cross-sectional and descriptive study was conducted in 39 athletes (12 women; 41.02 ± 14.96 years old [15.4–71.5]) of Southern Chilean teams participating in the Goalball National Championship. Seven questions from a questionnaire about injuries and illnesses during 4 weeks prior to the competition were analyzed through frequency distribution and measures of key trends. Results: The prevalence of prior injuries was determined as 64.1% ( n = 25), which influenced training in different ways. Sixty percentage of athletes thought these injuries would affect their performance during the championship. Finally, 25.64% ( n = 10) reported having a disease. Conclusions: To our knowledge, this is the first study determining past injuries and illnesses in athletes with visual impairments. This information is important to elaborate preventive strategies and to provide better medical support during competitions. Implications for practitioners: The multidisciplinary teams preparing athletes with visual impairments can use this information to develop preventive strategies to reduce injuries, improve sport performance, and provide better medical support during competitions.